TINGKAT ASPIRASI KARIR SISWA DI TINJAU DARI JENIS KELAMIN - Yusrial Chandra (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2017)
Career apathy is very important to support the future / career of students, because it is a demand in life. Career aspiration is an individual orientation towards the desired career goals according to the desired conditions or expectations. One of the factors that influence an individual's career orientation is gender. Problems related to gender or gender greatly affect the achievement of individual career goals, namely in men and women. This research attempts to see the description of career aspiration level of students of gender variables. This study aims to reveal and describe differences in the level of career aspirations of students in terms of gender. The type of research used is descriptive comparative. The hypothesis tested in this study is